Denseness of ergodicity for a class of volume-preserving flows - Bessa, Mário (2011)
We consider the class of C1 partially hyperbolic volume-preserving flows with one-dimensional central direction endowed with the C 1 -Whitney topology. We prove that, within this class, any flow can be approximated by an ergodic C2 volume-preserving flow and so, as a consequence, ergodicity is dense.